PENGARUH MODEL PEMBELAJARAN INDEX CARD MATCH TERHADAP HASIL BELAJAR IPS SISWA KELAS V SEKOLAH DASAR - Oktaviani, Rani; Lingga, Leny Julia (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to examine the effect of the Index Card Match learning model on fifth-grade students’ social studies learning outcomes at SDN 6 Pinggir. The research employed a quantitative approach using a pre-experimental method with a one-group pretest–posttest design. The population consisted of 47 students, and the sample was selected through purposive sampling, resulting in 22 students from Class V.A. Data were collected using multiple-choice test instruments. The hypothesis was tested using a paired samples t-test to determine the effect of the Index Card Match learning model on students’ learning outcomes. The results showed a significant improvement in students’ scores, with the mean increasing from 57.95 in the pretest to 87.55 in the posttest. The paired samples t-test indicated a significance value of 0.00, which is lower than 0.05, leading to the acceptance of the alternative hypothesis. In conclusion, the implementation of the Index Card Match learning model has a significant effect on improving fifth-grade students’ social studies learning outcomes at SDN 6 Pinggir.